Managing the ageing workforce in the East and the West - Flynn, Matt, 1969-; Chiva, Anthony, 1949-; Li, Yuxin, active 2017; Parry, Emma (The changing context of managing people, 2017)
Employers all over the world are engaged with implementing human resource management (HRM) policies in order to encourage and facilitate longer working lives for an aging workforce. While there has been some scholarly investigation into workplaces challenges and changes in both Europe and North America, there has been less engagement with the significant challenges facing Asian businesses and little assessment of the common themes and regional differences. Managing the Ageing Workforce in the East and the West brings together HRM specialists from both Eastern and Western perspectives in a unique collaboration. Each chapter explores the universal relevance of human resource interventions into extending working life, including phased retirement, healthy work environments and lifelong learning. The book assesses issues of implementation in differing cultural, intergenerational, institutional and family contexts. Rooted in a cross-cultural approach, the authors draw on a range of data from different geographic workforce contexts in order to identify over 150 variables relating to specific types of careers, including job content, employer policies, human capital, retirement plans, and quality of life expectations. Central to the study is measuring the complex relationship between individual workers' work and retirement expectations in relation to the differences in employer practices in the West and the East.The book will be essential reading for students and scholars of HRM and organizational studies, as well as human resource professionals, employers and chief executives, and employment and business consultants.